ANALYSIS OF MALPRACTICE CRIMINAL ACTS COMMITTED BY NURSES FROM A HEALTH LAW PERSPECTIVE - Sry Ningsih Saragih; Muhammad Arif Sahlepi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Malpractice is a significant issue in the health sector, where errors or negligence committed by medical personnel can cause serious harm to patients. In the context of Indonesian law, malpractice not only harms patients physically, but also has major legal implications. This analysis aims to examine the legal aspects and accountability related to criminal acts of malpractice in health law in Indonesia. Through this study, various laws and regulations governing medical practice, Law Number 17 of 2023 concerning Health, and the Criminal Code (KUHP), as well as administrative regulations governing the ethics and discipline of health workers are described. Malpractice liability can be categorized into three main forms: criminal, civil, and administrative. Criminally, medical personnel can be prosecuted if proven to have committed negligence that causes death or serious injury, in accordance with the articles in the Criminal Code. In the civil realm, patients who are harmed have the right to claim compensation through a lawsuit for unlawful acts (PMH). Meanwhile, administrative sanctions can be imposed by the relevant agencies if violations of professional standards and codes of ethics are found. This study concludes that legal regulations in Indonesia provide a clear framework for handling medical malpractice cases, although there is still a need to strengthen the legal protection mechanism for patients and more consistent law enforcement. Legal liability in malpractice cases includes preventive and repressive aspects, with the aim of providing justice for the injured party and maintaining the integrity of the medical profession.